Pengaruh Resiliensi Terhadap Work Engagement Pada Masinis Yang Bertugas Di Stasiun Tugu Yogyakarta - Damayanti, Ajeng Tyas; Handoko, Handoko (Politeknik Perkeretaapian Indonesia Madiun, 2018)
Travel safety is realized from the minimum number of train accidents that occur. This study is to determine the effect of resilience to work involvement in machinists on duty at Tugu Station in Yogyakarta. The study was conducted by conducting interviews to obtain preliminary data and ask to fill out the questionnaire provided. The results showed that 43% of respondents had low resilience, while the other 57% had high resilience. As many as 52% of machinists have high work involvement, while 48% have low work involvement. The correlation between them is at a moderate level of 0.627.